2003
DOI: 10.1186/1478-4491-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of perceptions of workplace violence in the Portuguese health care sector

Abstract: This article characterizes the problem of violence against health professionals in the workplace (VAHPITWP) in selected settings in Portugal. It addresses the questions of what types of violence are most frequent and who are the most affected health professionals.Three methodological approaches were followed: (i) documentary studies, (ii) a questionnaire-based hospital and health centre (HC) complex case study and (iii) semi-structured interviews with stakeholders.Of the different types of violence, all our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 0 publications
4
41
1
12
Order By: Relevance
“…Fato que sugere a influência das relações de gênero nessa determinação. De modo que, embora se atribua a ocorrência de violência entre as profissões consideradas mais perigosas, como a de vigilantes e policiais, os estudos têm chamado a atenção para a elevada prevalência do problema nas profissões tipicamente femininas, em particular as exercidas por mulheres mais jovens e com menor nível de escolaridade 6,7 .…”
Section: Introductionunclassified
“…Fato que sugere a influência das relações de gênero nessa determinação. De modo que, embora se atribua a ocorrência de violência entre as profissões consideradas mais perigosas, como a de vigilantes e policiais, os estudos têm chamado a atenção para a elevada prevalência do problema nas profissões tipicamente femininas, em particular as exercidas por mulheres mais jovens e com menor nível de escolaridade 6,7 .…”
Section: Introductionunclassified
“…In addition, the frequency of verbal mobbing experienced by academicians in our study was similar to that of another study [20] but it was lower compared to other two studies [17,25].These studies reported that the rate of verbal mobbing behaviors was between 82-90 %. Differences in the rate of mobbing in these studies may be a result of using different mobbing definitions, scales [21,25] settings and participants(academic staff, only academic nurses, only physicians [14] and differences perceptions of workplace violence [1,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…MPS is -a six fold Likert type-including 33 items classified into 4 dimensions. The 11 items (17-20, 22-26, 30,31)refer to "Isolation from work", the 9 items (5,10-14,16,21,29) refer to "assault to professional status", the 9items (1-4,6-9,15) refer to "assault to personality", and the 4 items (27,28,32,33) refer to "direct negative behaviors". The answers to the scale were scored as follows; 0=never or scarcely ever,1=once,2=a few times, 3=sometimes,4=often,5=always.…”
Section: Questionnairesmentioning
confidence: 99%
“…Research on labor violence in the health sector found that verbal violence is most frequent and is directed against the woman worker (13) .…”
Section: Discussionmentioning
confidence: 99%